Cultivating learning cultures: Building trust with apprentices in a Swiss telecommunications company - Antje Barabasch; Christina Donovan (International Journal for Research in Vocational Education and Training (IJRVET), 2026)
Context: In Switzerland, about two-thirds of young people start dual vocational education and training (VET) at around 15 years of age. Research shows that they are challenged in many ways during this phase of their lives and are therefore particularly vulnerable. Thus, supporting the transition of apprentices from school to the workplace environment requires careful attention. Trust is predicated upon the individual's willingness to be vulnerable, and as such enterprises which offer VET to young learners must consider how they structure trust-building processes into their learning cultures.~ Method: A case study approach was adopted to investigate apprenticeship provision in the largest telecommunications company in Switzerland. Over the course of one year, 24 semi-structured interviews and observations were conducted with apprentices, coaches and managers. The qualitative data were processed through condensation, building categories and paraphrasing, by following Bohnsack's formulative interpretation method.~ Findings: The initial investigation of the learning culture within the company found that a cooperative culture of trust is crucial for educational success. In this context, the way relationships were formed in the workplace was particularly significant. Expressed through~constructive feedback and error culture, learners were supported to take risks and learn from their mistakes. Active participation was also highly valued, leading to a felt sense of recognition and belonging to the organisation.~ Conclusion: Trustful relationships within the apprenticeship proved to be a foundational conviction in the company, and while it must be noted that trust is not the sole predictor of success in VET, the learning culture facilitated by trust-building processes afforded opportunities for apprentices to take ownership of their own learning, through negotiated outcomes; leading to creative autonomy and contributions that were to the benefit of the enterprise.
Keywords: 330; Culture of Trust; Innovation; Learning Culture; Vocational Education and Training; VET; Case Study